2016
DOI: 10.1016/j.tet.2016.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) catalyzed reductive radical cyclization reactions of bromoacetals in the presence of NaBH4: optimization studies and mechanistic insights

Abstract: 5-Exo-trig radical reductive cyclization reactions of bromoacetals are catalyzed by iron in the presence of the reducing agent NaBH 4. Both iron(II) and iron(III) were found to effectively mediate these reactions. As shown by cyclic voltammetry, iron(III) can be reduced to an iron(II) precatalyst before passing through an identical reaction mechanism in which monoelectronic activation of the substrate would occur by an anionic hydridoiron(I) complex. Further studies have established that both the substrate (io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
2
14
0
Order By: Relevance
“…Fensterbank et al. disclosed an elegant method to reduce the halogenoacetals in presence of 10 mol % of FeCl 2 and NaBH 4 ,,, Oshima et al. utilized PhMgBr for the activation of FeCl 2 .…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…Fensterbank et al. disclosed an elegant method to reduce the halogenoacetals in presence of 10 mol % of FeCl 2 and NaBH 4 ,,, Oshima et al. utilized PhMgBr for the activation of FeCl 2 .…”
Section: Methodssupporting
confidence: 85%
“…It has been proposed in the previous studies that the Fe(I) is generated upon mixing either FeCl 2 and Zn or FeCl 2 and NaBH 4 ,,, though Fe(0) cannot be ruled out. It is also noticed that the alkyl halide is intact in the absence of either FeCl 2 or Zn (entries 9 and 10, Table ).…”
Section: Methodsmentioning
confidence: 96%
“…First, we examined the reactivity of iodoacetal 1 a as model substrate towards the iron hydride complex [HFe (II) Cl(dppe) 2 ], prepared according the procedure reported by Sacco from FeCl 2 and dppe in the presence of NaBH 4 . After the reaction optimisation phase (nature of the reducing agent (NaBH 4 or NaBH 3 CN) or the amount of reducing agent employed (10–150 mol %)), we showed that treatment of iodoalkene 1 a by 10 mol % HFe (II) Cl(dppe) 2 in acetonitrile (0.5 M) at 50 °C under reducing conditions (1 equivalent of NaBH 4 ) gave the reductive cyclisation product (70 %) with a 87 : 13 diastereoselectivity ratio. Conversely, the same experiment repeated with bromacetal 1 b was unsuccessful and left the substrate unchanged whatever the order of reagent introduction (Scheme ) …”
Section: C−x Activation Via Iron Catalysismentioning
confidence: 99%
“…As already showed, [HFe (I) Cl(dppe) 2 ] − can be formed by SET from NaBH 4 and then reduce 1 a but not 1 b . The borane (BH 3 ) that is liberated may participate to the dppe ligand dissociation from [HFe (II) Cl(dppe) 2 ] and would be irreversibly trapped by dppe as indicated by the formation of 1,2‐bis(diphenylphosphino)ethane bisborane (evidenced by 31 P NMR, vide supra ) ,. A new dppe‐free complex with acetonitrile as ligand such as [HFe (II) Cl(CH 3 CN) n ] may be formed and subsequently activated by NaBH 4 as a phosphine‐free anionic [HFe (I) Cl(NCCH 3 ) 2 ] − complex which may act as the reductant of the organic halide by SET process (Scheme ).…”
Section: C−x Activation Via Iron Catalysismentioning
confidence: 99%
See 1 more Smart Citation